ANALISIS NILAI KONDISI LAPIS PERKERASAN JALAN PADA RUAS JALAN ARTERI PRIMER PADA JALAN LABUANG KABUPATEN BURU SELATAN: (Analysis of Road Pavement Condition Values on Primary Arterial Road Sections on Laburan Road, South Buru Regency) - Assagaf, Sjaid S. Fais; Sudarman, Andi; Yani, A. (Uniqbu Journal of Exact Sciences, 2023)
The road damage greatly affects the smooth flow of traffic and the safety and comfort of road users, especially on the Primary Arterial road section in South Buru Regency, Namrole City. The issues raised What are the types of road damage that occurred on the Laburan-Kilo Satu road and what is the value of the road pavement condition on the Laburan-Kilo One road. So that it can be known the type of road damage that occurred on the Laburan-Kilo Satu road and the road pavement condition value on the Laburan-Kilo Satu road. This research was conducted to identify the type and level of damage that occurred in the primary arterial road. The method used is the Bina Marga method, namely the calculation of the type of road damage and the type of handling, by calculating the type of damage and calculating the LHR that crosses the observation point. The results of visual observations in the field obtained damage area, depth, crack width and type of damage that will be used as data for damage handling with the 1995 Bina Marga Method on the Laburan-Kilo One road section in South Buru Regency with a road length of 1,500 meters divided into 15 stations including the type of roughness found on the road section on the Laburan-Kilo Satu road Namrole City, South Buru Regency Cracked Alligators, Surface Roughness or Surface Defects, Holes and Collapsed. The largest value of road damage is in STA 800-900, amounting to 0.520 km2. Meanwhile, the smallest road damage was at STA 600-700 of 0.27 km2. The dominant type of damage found on this road is damage to crocodile skin cracks with damage intervals of 1 m2 to 50 m2.